The Development of Innovative Capacity of R&D Institutions of Ukraine as a Result of Participation in the Project of the Seventh Framework Program of the European Union - Nikitin, Yu.A.; Rukas-Pasichnyuk, V.G. (Science and Innovation, 2024)
The paper considers the successful experience of the V.M. Bakul Institute for Superhard Materials of the NAS of Ukraine in the Start project (contract no. 295003) within the 7th Framework Program of the European Union, which has had a favorable impact on raising the research and innovation potential and on the implementation of the Institute’s innovations to the economy of Ukraine and Europe.